2021
DOI: 10.1007/s40279-021-01612-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Training on Anabolic and Catabolic Hormones with Advanced Age: A Systematic Review

Abstract: Background Ageing is accompanied by decreases in physical capacity and physiological regulatory mechanisms including altered hormonal regulation compared with age-matched sedentary people. The potential benefits of exercise in restoring such altered hormone production and secretion compared to age-matched physically inactive individuals who are ageing remains unclear. Objectives The aim of this systematic review was to summarise the findings of exercise tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 95 publications
0
11
0
Order By: Relevance
“…Exercise training affects the production of gonadal sex steroid hormones, with some studies reporting increases in total and free testosterone levels after a bout of heavy resistance exercise in men, whereas responses in women are not clear (426)(427)(428). This effect varies by age, training status, mode, intensity, and volume of exercise training.…”
Section: Fat-free Mass: Resistance and High-intensity Trainingmentioning
confidence: 99%
“…Exercise training affects the production of gonadal sex steroid hormones, with some studies reporting increases in total and free testosterone levels after a bout of heavy resistance exercise in men, whereas responses in women are not clear (426)(427)(428). This effect varies by age, training status, mode, intensity, and volume of exercise training.…”
Section: Fat-free Mass: Resistance and High-intensity Trainingmentioning
confidence: 99%
“…From a physiological point of view, physical activity has a number of benefits, including the prevention of decreased cardiovascular system function, sarcopenia, decreased bone density, increased blood pressure, etc. The mechanism may be that exercise increases the level of anabolic hormones in elderly people [30].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review of interventional studies with men and women (≥40 years), exercise training has been shown to provide an increase in the plasmatic anabolic hormones, including testosterone, human growth hormone, insulin-like growth factor-1, and dehydroepiandrosterone sulfate ( Zouhal et al, 2021 ). However, different meta-analyses evaluating exercise interventions have not found an increase in the baseline of total and free testosterone from adults and the elderly ( Hayes and Elliott, 2018 ; Potter et al, 2021 ).…”
Section: Anabolic-androgenic Steroids When Exercise Seems Ineffective...mentioning
confidence: 99%